PELATIHAN PEMASARAN PRODUK PASAR MELALUI MARKET PLACE DALAM RANGKA SEKOLAH PASAR BAGI PEDAGANG PASAR REJOWINANGUN MAGELANG - Fahmi Medias; Ahmad Muflih Akbar; Niko Hantoro; Ahmad Imaduddien Akmal; Ibnu Fajar; Farizi Makruf (Jurnal Pengabdian Masyarakat Khatulistiwa, 2020)
Rejowinangun Market which is located in the heart of Magelang City is one of the traditional markets that has historical attachment to the socio-economic development of the people of Magelang City. The inability of traditional markets to compete with modern markets is a problem that must be resolved immediately. One example of a problem that occurs in business management is the lack of use of online media to market goods in the market. Market schools for traders are implemented to provide solutions to these problems so as to improve the ability of traders in terms of business management and can market goods through online media, so that transactions between sellers and buyers can occur directly (in the market) and indirectly (online store) . Community empowerment through the Participatory Rural Apraissal (PRA) model is very effective in helping market traders improve competitiveness with modern markets. The results of this market school show that the implementation of business management for traders has a significant influence in increasing business profits, increasing market competitiveness by optimizing online stores for market traders 'products, and increasing the marketing mix of market traders' products.